Предмет: Алгебра,
автор: Olov11111111
1.Упростите выражения :
а)(4х^2+3y)(y-2x^2)
b)(a^2-b^2)(2a+b)-ab(a-b)
c)(5x+2)(x^2-2x-3)
d)-3b(1-b^2)(5b+2)
2.Докажите тождество :
х^4-1=(x+1)(x^3-x^2+x-1)
Ответы
Автор ответа:
0
А) 4х^2у-8х^2+3у^2-6х^2у= -2х^2у-8х^4+3у^2
Б) 2а^3+ба^2-2аб^2-Б^3-а^2+аб^2=2а^3-аб^2-Б^3
В)5х^3-10х^2-15х+2х^2-4х-6=5х^3-8х^2-19х-6
Г) (-3б+3б^3(5б+2))=-15б^2-6б+15б^4+6б^3
Х^4-1=Х^4-Х^3+Х^2-Х+Х^3-Х^2+х-1
Х^4-1=Х^4-1
Похожие вопросы
Предмет: Литература,
автор: danaurazalina1982
Предмет: Математика,
автор: morfg
Предмет: Алгебра,
автор: davamarl
Предмет: Математика,
автор: shrek250102